Belowground organs and bud bank: Insights on morphoanatomical functional traits related to fire - Bombo, Aline Bertolosi [UNESP]; Appezzato-da-Glória, Beatriz; Martins, Raquel [UNESP]; Fidelis, Alessandra [UNESP] (Springer Nature, 2024)
The presence of belowground organs with buds and carbohydrate storage is typical of perennial plants in fire-prone ecosystems. The bud-bearing storage organs allow regeneration after fire, and they may lose their regeneration capacity if the disturbance is excluded, because of the depletion in the bud bank. We assessed the morphology, anatomy, and storage of carbohydrates in the belowground organs of eight perennial species from open savannas and analyzed their bud banks at different fire frequencies (annual, biennial, and exclusion). Xylopodium was found in all the study species as bud-bearing organ, associated with proliferated storage parenchyma tissue, often in the tuberous roots. We found that bud bank size varied according to different fire frequencies for only half of the studied species (most forbs), and a tendency for lower bud bank sizes in fire-excluded areas was found for all shrub species. Our study highlights the significance of bud-bearing storage organs, particularly xylopodium, and that the species-specific responses of bud bank size to different fire frequencies underscore the need to consider individual plant strategies when analysing fire effects, emphasizing the critical role of belowground organs in sustaining these ecosystems.
Keywords: Belowground storage; Disturbance; Persistence; Resprouting; Xylopodia